2021
DOI: 10.3390/bios11060178
|View full text |Cite
|
Sign up to set email alerts
|

Silicene Quantum Capacitance Dependent Frequency Readout to a Label-Free Detection of DNA Hybridization— A Simulation Analysis

Abstract: The use of deoxyribonucleic acid (DNA) hybridization to detect disease-related gene expression is a valuable diagnostic tool. An ion-sensitive field-effect transistor (ISFET) with a graphene layer has been utilized for detecting DNA hybridization. Silicene is a two-dimensional silicon allotrope with structural properties similar to graphene. Thus, it has recently experienced intensive scientific research interest due to its unique electrical, mechanical, and sensing characteristics. In this paper, we proposed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In conclusion, it has been inferred that metal decorated silicene can be a potential candidate for distinguishing DNA/RNA nucleobases. Rahman et al [38] have proposed an ISFET model, which is made of silicene and electrolyte layers that help one to detect DNA hybridization. It is to be noted that we would like to mention that DNA hybridization is a process which provides the genetic differences between two organisms.…”
Section: Studies Of Dna Sequencing By Silicenementioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, it has been inferred that metal decorated silicene can be a potential candidate for distinguishing DNA/RNA nucleobases. Rahman et al [38] have proposed an ISFET model, which is made of silicene and electrolyte layers that help one to detect DNA hybridization. It is to be noted that we would like to mention that DNA hybridization is a process which provides the genetic differences between two organisms.…”
Section: Studies Of Dna Sequencing By Silicenementioning
confidence: 99%
“…In conjunction with the low thermal conductivity of silicene, these findings indicate that silicene-based nanostructures could be the basis of more efficient TE devices. Recently, it has been found that silicene can be used very efficiently as biosensor [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the most important are fluorescently labeled target microscopy [ 59 ], laser scanner [ 60 ], Surface-Enhanced Raman spectroscopy (SERS) [ 61 , 62 ]; whose methods can be also classified as optical methods. Other well-known methods use enzymatic polymerization [ 63 ], biofunctionalized ion-sensitive field-effect transistors [ 64 ] and varieties of methods based on different imaging systems [ 65 ]. The biomolecules with corresponding tags as enzymatic, fluorescent, radioactive etc.…”
Section: Biosensor Technologymentioning
confidence: 99%
“…By using an ion-sensitive field-effect transistor (ISFET) structure with silicene layers and electrolyte, Sazzadur Rahman et al have designed a sensor with the capability of label-free detection of deoxyribonucleic acid (DNA) for disease-related gene expression 37 . Also, Kharadi et al reported an optical detector using silicene-MoS 2 heterojunction with high efficiency 38 .…”
Section: Introductionmentioning
confidence: 99%